Obesity and Overweight Problem in Children (7-12 years) Coming from Affluent Families in Dhaka city in Bangladesh (Bangladesh Journal of Nutrition, 2013)
The study find-out the obesity and overweight problems in children (7-12 yrs) coming from affluent families in Dhaka city in Bangladesh. Mean height and weight were 142.61±10.43cm and 40.50±11.95kg respectively. One fourth (25%) of the students were found to be obese and 21.88% were overweight according to their BMI percentile. Among boys 31.43% were obese and for the girls it was 7.69%. Among boys 18.57% are overweight and for the girls it was 30.76%. Male students were both obese and overweight than the female. Most (63.64%) of the male obese students were in the age group of 7.92-9.17 yrs and 10.5-11.67 yrs whereas most (62.5%), n=5 0f 8) of the female obese students were in the age group of 7.92-10.42yrs. Based on WAZ, 12.5% of the students were found to be obese and 10.41% were overweight. Among boys 28.34% are obese and for the girls it was 6.82%. Among boys 25.71% are overweight and for the girls it was 35.23%. Male students are more obese than the female. Based on HAZ One sixth (5.20%) of the students were found to be obese and 17.70% were overweight. Among boys 28.34% are obese and for the girls it was 6.82%. Among boys 25.71% are overweight and for the girls it was 35.23%. Based on WHZ one sixth (4.23%) of the students were found to be obese and 8.51% were overweight. Among boys 28.34% are obese and for the girls it was 6.82%. Among boys 25.71% are overweight and for the girls it was 35.23%. Male students are more obese than the female. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14038 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.77-82